На Верхней Масловке: повести и рассказы / Дина Рубина - Рубина Дина Ильинична (Эксмо, 2004)
Экземпляры: Аб (20160302) / Инвентарный номер: 103675 / Цена: 100.00 / Авт.знак: Р 82 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6